2011
DOI: 10.1590/s0102-695x2011005000124
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-guided evaluation of central nervous system effects of citronellal in rodents

Abstract: Abstract:The central nervous system (CNS) depressant and anticonvulsant activities of citronellal (CT) were investigated in animal models. The CT in doses of 100, 200 and 400 mg/kg injected by i.p. route in mice caused a significant decrease in the motor activity of animals when compared with the control group. The highest dose of CT significantly reduced the remaining time of the animals on the Rota-rod apparatus up to 2 h. Additionally, CT at doses 100, 200 and 400 mg/ kg (i.p.) was also capable to promote a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Therefore, the CT-βCD is able to activate CNS areas, specifically those related to pain inhibition. The opioid and glutamate systems are probably involved in the anti-hyperalgesic effect observed in the present study, as suggested previously by Melo et al (2011Melo et al ( , 2010. Therefore, Skyba and Sluka (2002) used NMDA and non-NMDA receptor antagonists and noted that both are involved in the maintenance of hyperalgesia in chronic muscle pain.…”
Section: Accepted Manuscriptsupporting
confidence: 83%
“…Therefore, the CT-βCD is able to activate CNS areas, specifically those related to pain inhibition. The opioid and glutamate systems are probably involved in the anti-hyperalgesic effect observed in the present study, as suggested previously by Melo et al (2011Melo et al ( , 2010. Therefore, Skyba and Sluka (2002) used NMDA and non-NMDA receptor antagonists and noted that both are involved in the maintenance of hyperalgesia in chronic muscle pain.…”
Section: Accepted Manuscriptsupporting
confidence: 83%
“…It has been observed that many monoterpenes present a reduction of locomotor activity (Passos et al 2009) by an inhibitory effect on the CNS or by a non-specific muscle relaxation effect (Melo et al 2011b). Thus, these activities can reduce the motor coordination response, invalidating the nociceptive behavioral tests (De Sousa et al 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that MEKR induces antihyperalgesic effect in the mechanical hyperalgesic models suggests that MEKR can block the neural transmission of pain, like other drugs do, and may induce analgesia. Moreover, it has been observed that many compounds derived from medicinal plants present a reduction of locomotor activity (Le Bars et al, 2001) by an inhibitory effect on the central nervous system (CNS) or by a non-specific muscle relaxation effect (Melo et al, 2011). Thus, these activities can reduce the motor coordination response, invalidating the nociceptive behavioral tests (de Sousa et al, 2006).…”
Section: Discussionmentioning
confidence: 99%